European diabetes research and its funding, 2002–2013. Issue 10 (1st August 2017) - Begum, M.; Lewison, G.; Sommariva, S.; Ciani, O.; Tarricone, R.; Sullivan, R.
Abstract: Aim: This study examined the outputs of research papers in diabetes from 31 European countries between 2002 and 2013, and their funding. Methods: Diabetes research papers in the Web of Science were identified by means of a filter based on journals and title words. For 2009–2013 papers, the funders were coded to show their sector and nationality. Results: Europe published 40 547 diabetes papers in the 12 years between 2002 and 2013. Denmark, Sweden and Finland published the most relative to their wealth, but the UK published the most absolutely despite an apparently low burden (as measured by disability‐adjusted life years). The largest source of funding was government (30%), followed by the non‐profit sector (18%) and industry (13%). The European Commission supported 2.7% of papers, but more in Latvia (33%) and Estonia (16%). Based on an estimated cost per paper of €260 000, the annual research expenditure in Europe was approximately €986 million in 2013. Conclusions: The European diabetes burden in disability‐adjusted life years increased by one third between 2002 and 2012, but its output of research papers has decreased from 44% to 36% of the world total. This decrease needs to be reviewed in the context of European non‐communicable disease research policy. What's new?: European diabetes research has declined from 44% of world output in 2002 to 33% in 2015 while the burden has increased from 2.0% to 2.6% of disability‐adjusted life years in 10 years. Outputs mostly correlate with gross domestic product – Scandinavia performs well except for Norway; France, Lithuania and Romania also do less well. Funding between subject areas varies with high levels on latent autoimmune disease of adults and maturity‐onset diabetes of the young; there is very little on foot problems. Main funding sources are government (30%), private–non‐profit organizations (18%, especially in the UK) and industry (13%, notably from Novo Nordisk).